Mogroside IIE Inhibits Digestive Enzymes via Suppression of Interleukin 9/Interleukin 9 Receptor Signalling in Acute Pancreatitis - Xiao, Juan; Huang, Kai; Lin, Houmin; Xia, Zhijia; Zhang, Jing; Li, Dianpeng; Jin, Junfei (Frontiers in Pharmacology, 2020)
The incidence of pancreatitis (AP) is increasing and there is no specific treatment available. Intracellular digestive enzyme activation is a key event in the pathogenesis of AP downstream of cytosolic calcium overload and impaired autophagy. Siraitia grosvenorii (Swingle) was used in Traditional Chinese Medicine to reduce inflammation and facilitate bowel movement. The bioactive components of this plant show hypolipedimic, antidiabetic, antifibrotic activity and have been used against pancreatic cancer. Here, we examined whether mogroside IIE, a major bioactive component of unripe S. grosvenorii fruit, can protect against AP. We found that mogroside IIE decreased the activity of trypsin and cathepsin B induced by cerulein plus lipopolysaccharide (LPS) in the pancreatic acinar cell line AR42J and primary acinar cells in a dose- and time-dependent manner. Mogroside IIE treatment decreased the levels of serum lipase and serum amylase in mice injected with cerulein plus LPS without influencing inflammation significantly. A multi-cytokine array revealed that mogroside IIE decreased the level of interleukin 9 (IL-9) in AP mice. Exogenous IL-9 eliminated the mogroside IIE induced reduction of trypsin and cathepsin B activity and reversed the inhibition of cytosolic calcium and modulation of autophagy mediated by mogroside IIE. An IL-9 receptor antibody neutralized the effect of IL-9, restoring mogroside IIE activity. The mogroside IIE targeted IL-9 may partially arise from Th9 cells. Taken together, we provide experimental evidence that mogroside IIE ameliorates AP in cell models and mice through downregulation of the IL-9/IL-9 receptor pathway.